Comparative Analysis of Machine Learning Algorithms for Credit Card Fraud Detection - Ignatious, Jerin; Kulkarni, Yogita; Bari, Shruti; Naglot, Deepali (International Journal of Computer Sciences and Engineering, 2020)
In this age of growing digitization, many of our day to day activities are being transformed with the help of the internet and everything is now available online. With the advent of the internet, nowadays online transactions have become an important and necessary part of our lives. As the number of transactions are increasing, the number of fraudulent transactions are also increasing rapidly. To reduce fraudulent transactions, machine learning algorithms like Local Outlier Factor and Isolation Forest are discussed in this paper. An online dataset is used to implement and test these algorithms. Finally with comparative analysis we tried to conclude which algorithm works better.